2015
DOI: 10.1371/journal.pone.0116879
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits Enterovirus 71 Replication and Pro-Inflammatory Cytokine Secretion in Rhabdosarcoma Cells through Blocking IKKs/NF-κB Signaling Pathway

Abstract: Polydatin and resveratrol, as major active components in Polygonum cuspidatum, have anti-inflammatory, antioxidant and antitumor functions. However, the effect and mechanism of polydatin and resveratrol on enterovirus 71 (EV71) have not been reported. In this study, resveratrol revealed strong antiviral activity on EV71, while polydatin had weak effect. Neither polydatin nor resveratrol exhibited influence on viral attachment. Resveratrol could effectively inhibit the synthesis of EV71/VP1 and the phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 50 publications
1
65
0
1
Order By: Relevance
“…of 5 and incubated at 37 C and 5 % CO 2 for 5 days until virus-induced the CPE was observed in control wells. Subsequently, an MTT assay with minor modifications was performed for the determination of cell viability [88]. Briefly, after removal of the medium, the cells were washed with PBS and 100 µl of fresh medium containing MTT (3-[4.5-dimethylthiazol-2-yl]À2,5-diphenyl tetrazolium bromide; Sigma Aldrich; 0,5 mg ml À1 ) was added to each well.…”
Section: Methodsmentioning
confidence: 99%
“…of 5 and incubated at 37 C and 5 % CO 2 for 5 days until virus-induced the CPE was observed in control wells. Subsequently, an MTT assay with minor modifications was performed for the determination of cell viability [88]. Briefly, after removal of the medium, the cells were washed with PBS and 100 µl of fresh medium containing MTT (3-[4.5-dimethylthiazol-2-yl]À2,5-diphenyl tetrazolium bromide; Sigma Aldrich; 0,5 mg ml À1 ) was added to each well.…”
Section: Methodsmentioning
confidence: 99%
“…Resveratrol has exerted immunomodulating effects in various studies ( Table 2) [46][47][48]. Resveratrol modulates immune response against pathogens like viruses, bacteria, and some toxic materials.…”
Section: Immunomodulating Effectsmentioning
confidence: 99%
“…Nencioni et al (2003) demonstrated that GSH inhibited expression of viral matrix protein, and inhibited virally induced caspase activation and Fas upregulation during influenza virus infection. Zhang et al (2015) also found that resveratrol, which has antiinflammatory, antioxidant and antitumour functions, inhibited EV71 replication and cytokine secretion in EV71-infected RD cells through blocking the Ik B kinase/ NFk B signalling pathway. Other authors thought that biochanin A affected H5N1 viral replication by inhibiting the activation of signalling molecules involved in virusinduced signalling, including AKT, extracellular regulated kinase 1/2 and NFk B (Pinto et al, 2011;Sithisarn et al, 2013).…”
Section: Discussionmentioning
confidence: 88%